Safety Assessment of Nutraceuticals - Rao, Koppal Suryanarayana (Biology, Engineering, Medicine and Science Reports)
Nutraceuticals are products isolated from foods that are generally sold in medicinal forms. They are defined as any food (or part thereof) which provides health benefits – including prevention and treatment of disease – in addition to the basic nutritional value found in foodstuff. Nutraceuticals are of particular interest as a way to reduce the expensive, high-tech disease treatment approaches currently employed in developed countries.